Psychosocial Interventions as Mental Health Support for Children and Adolescents with Special Needs: A Systematic Literature Review - Hutasoit, Dame Triulina; Hendriani, Wiwin (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to identify the importance of mental health support for children and adolescents with special needs through a Systematic Literature Review (SLR) approach. The SLR process involved the identification, selection, and analysis of articles obtained from the Scopus database using the keywords “children,” “adolescents,” and “special needs.” Out of an initial 55 articles, 10 relevant studies were selected, comprising longitudinal, qualitative, and experimental research published in Q1 to Q4 indexed journals. These studies examined psychosocial interventions such as school-based counseling, cognitive-behavioral therapy, and social skills training. The findings indicate that sustained and contextually adapted interventions have a positive impact on psychological well-being, social adaptation, and academic achievement among children and adolescents with special needs. Active support from families, educational institutions, and communities emerged as key factors contributing to the success of these interventions. This review highlights the necessity of integrating interdisciplinary frameworks in policy and intervention development and encourages further research exploring the effectiveness of cross-cultural and longitudinal approaches.